Wasei-Eigo Analysis on Instagram Social-Media: a Review of Sociolinguistics Study - Berliana Fajrin; Yuni Masrokhah (Jurnal Lingua Idea, 2022)
Wasei-eigo is a word or combination of words originating from English and then being adopted into a Japanese vocabulary with a different meaning from the original speaker in other words wasei-eigo is English made by the Japanese. This study aims to describe the process of wasei-eigo formation and classify the types of wasei-eigo found on Instagram social media. The main theory is based on the theories of Shibasaki, Tamoka, and Takatori. The method used in this research is the descriptive qualitative method. The data source comes from the captions of Japanese Instagram social media users uploaded from 2021 to early 2022. The results show that from the 45 wasei-eigo data studied, there are four processes of wasei-eigo formation: affixation, merging, cutting, and borrowing. In the classification, there are 15 data included in Imizurekata, 11 data included in Tanshukukata, 2 data included in Junwaseikata, and 12 data included in Eigohyougenfuzaikata. This is related to the many uses of English adopted in the life of Japanese society. Wasei-eigo can be found in various aspects of life such as social, cultural, economic, or technological with the initial purpose of being a commercial form of a product and meeting the needs of the lexical gaps in the Japanese language.